Integrating virological data in vaccine effectiveness studies Proposal to IMOVE - Rodrigues, Ana Paula (2015)
When is it valuable to estimate vaccine effectiveness against a specific genetic group? - Clade of interest has a low proportion of cases but there is a suspicion of low VE (e.g.: newly circulating clade at the end of the season) - Several clades are circulating (VE against clade differs to the VE against influenza subtypetilineage) - Vaccine effectiveness is low